Ball and stick fun model kit / Munirah Onn ... [et al.] - Onn, Munirah; Zaiton, Siti Nurul’Ain; Azman, Hairul Amiza; Zainuddin, Aznilinda; Mohd Sani, Noor Faezah; Mohammad IIiyas, Siti Mariam (Universiti Teknologi MARA, Perak, 2020)
Chemistry is one of the most important subjects and perceived as a killer subject in Malaysia. Crystal and chemical bonding topics were included in major examinations such as SPM and STPM, as well as in Diploma and Degree levels of studies. In chemistry, class theory is a common teaching method for crystal structure and chemical bonding topics. Thus, this kit introduces a new teaching method where students need to produce the chemical bonding or crystal structure by using the ball and stick model. The colored balls represent the atoms, and the sticks represent the bonds that hold them together. It is a complete set of tinker toys to represent how molecules look. This kit box has been sold at the price of RM19.90 and it contains 200 pieces of molecular model kit, including 70 atoms (ball), 100 bonds (stick) and 30 parts for lone pairs. It comes with an instruction CD, notes and exercises thus serves as a fun learning tool kit for students from secondary school to university level. The parts in the kit can be taken apart and rebuilt or can be used for display or teaching specific crystallographic or structural concepts. The different colored balls represent atoms of different elements. The survey has been conducted and 100% diploma students agree that this kit is fun and help them in understanding the topic.